1992
DOI: 10.2105/ajph.82.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the break-even point for smoking cessation programs in pregnancy.

Abstract: BACKGROUND. Successful programs to help pregnant women quit smoking have been developed and evaluated, but formal smoking cessation programs are not a part of care at most prenatal sites. The cost of such programs may be an issue. Considering the costs of adverse maternal and infant outcomes resulting from smoking, we estimated there would be an amount of money a prenatal program could invest in smoking cessation and still "break even" economically. METHODS. A model was developed and published data, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Because our analysis is based on a much larger population database than earlier estimates, the level of uncertainty in our estimates is much lower than earlier studies. 12,13,49,50 As a check on our results, we calculated the mean excess hospital cost per live birth using similar cost data for Maryland, 51 which covered all recorded discharges from Maryland nonfederal hospitals in 1995 for newborn admissions and transfers of newborns within 7 days of birth. The average US excess cost per live birth to a maternal smoker were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Because our analysis is based on a much larger population database than earlier estimates, the level of uncertainty in our estimates is much lower than earlier studies. 12,13,49,50 As a check on our results, we calculated the mean excess hospital cost per live birth using similar cost data for Maryland, 51 which covered all recorded discharges from Maryland nonfederal hospitals in 1995 for newborn admissions and transfers of newborns within 7 days of birth. The average US excess cost per live birth to a maternal smoker were similar.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Two studies investigated interventions that had previously been described in the literature, 53 54 while four studies modelled hypothetical interventions. 44 45 47 49 Comparator interventions among studies with primary data collection were self-help materials (four studies); 41 43 48 52 brief advice (four studies); 41 48 51 52 and standard UK National Health Service treatment (see online supplementary file 3 for details) (two studies). 33 35 The following were used by one study each, placebo patches with behavioural support; 32 no intervention; 46 and a cessation programme that was not defined.…”
Section: Resultsmentioning
confidence: 99%
“… 33 35 The following were used by one study each, placebo patches with behavioural support; 32 no intervention; 46 and a cessation programme that was not defined. 42 For studies without primary data collection, seven used an assumed or spontaneous background quit rate, 40 44 45 49 50 53 55 while one study used multiple comparators which included low intensity behavioural support, non-conditional incentives and usual care (not defined). 54…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that if a woman quits smoking early in pregnancy the risk of an adverse fetal outcome decreases toward that of a non-smoker (Dolan- Mullen, Ramirez, & Groff, 1994;Li, Windsor, Perkins, Goldenberg, & Lowe, 1993;Sexton & Hebel, 1984). Studies have also established the cost-effectiveness of programs for smoking cessation in pregnancy (Ershoff, Quinn, Dolan-Mullen, & Lairson, 1990;Melvin, 1997;Shipp, Croughan-Minihane, Petitti, & Washington, 1992) and have determined that for every dollar spent on smoking cessation, $6 can be saved in longterm costs (Marks, Koplan, Hogue, & Dalmat, 1990). Despite this, few comprehensive programs are available to the commercially insured population to help with smoking cessation in pregnancy (Barker, Robinson, & Rosenthal, 2000), and while obstetric providers have been sensitized to the need to identify smokers, they are not systematically counseling pregnant smokers (Helwig, Swain, & Gottlieb, 1998;Mullen, Pollak, Titus, Sockrider, & Moy, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…MCOs may be reluctant to implement these systems changes because of a delay in realized cost savings or failure to realize savings at all because of rapid member turnover (Warner, 1998). Pregnancy, however, is a time when the health benefits and cost savings of smoking cessation may be realized almost immediately because of improved birth outcomes and improved infant health (Ershoff et al, 1990;Melvin, 1997;Shipp et al, 1992). Therefore, providing a smoking-cessation benefit for pregnant women can have public health benefits as well as managed-care financial benefits.…”
Section: Introductionmentioning
confidence: 99%